Proceedings of the national workshop on food-based strategies for improving nutrition in Bangladesh, April 26-27, 1998 - Iqbal, Anwar; del Ninno, Carlo; Thilsted, Shakuntala H. (Ministry of Food, Government of Bangladesh, 1999)
This workshop on “Food-Based Strategies for Improving Nutrition in Bangladesh” has been organized as a follow up to the “International Workshop on Prevention and Control of Micronutrient Malnutrition through Food-Based Action in the SAARC Countries” held in Dhaka in November 1997. During that workshop it was recognized that micronutrient malnutrition is a serious problem in the SAARC countries and that food-based approaches play a vital role in the reduction of malnutrition. It was also suggested to conduct regional workshops on the progress of food-based approaches for improving nutritional status.